2002
DOI: 10.1097/00054725-200207000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Role of Appendicitis and Appendectomy in the Pathogenesis of Ulcerative Colitis: A Critical Review

Abstract: Besides a genetic predisposition, a causal role of various environmental factors has been considered in the etiology of ulcerative colitis (UC). The association between appendectomy and UC has recently been the subject of intense scrutiny in the hope that it may lead to the identification of important pathogenetic mechanisms. Published data from animal models of colitis demonstrated reduction in experimental colitis after appendectomy, especially if performed at an early age. Several epidemiological case contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
1
9

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(68 citation statements)
references
References 73 publications
(109 reference statements)
2
55
1
9
Order By: Relevance
“…For instance, a meta-analysis evaluating 13 case-control studies, and the combined results of the individual studies suggest that removal of the appendix reduces the risk of developing ulcerative colitis by 69% [4]. Appendectomy in the dextran sodium sulfate mouse model, and T cell receptor-·-deficient mouse model of colitis, protects animals from establishing severe inflammatory disease [10,11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, a meta-analysis evaluating 13 case-control studies, and the combined results of the individual studies suggest that removal of the appendix reduces the risk of developing ulcerative colitis by 69% [4]. Appendectomy in the dextran sodium sulfate mouse model, and T cell receptor-·-deficient mouse model of colitis, protects animals from establishing severe inflammatory disease [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, appendectomy is protective for patients against the development of ulcerative colitis, and has been reported to reduce the risk of acquiring intestinal disease [4][5][6]. Moreover, a Swedish meta-analysis by Andersson [7] has demonstrated a negative association between appendectomy and ulcerative colitis, as well as Crohn's disease.…”
Section: Introductionmentioning
confidence: 99%
“…Findings from a registry-based study in Sweden indicate that it is appendicitis, and not the appendicectomy as such, that is associated with a decreased risk of UC, giving further credence to such a hypothesis [97] . In addition, in a meta-analysis [98] from 2002, a pooled protective effect was reported for an appendectomy in UC in 17 case-control studies with an OR of 0.31 (95% CI 0.26-0.37). All these studies have suggested that alterations in mucosal immune responses leading to appendicitis or resulting from appendectomy may negatively affect the pathogenetic mechanisms of UC.…”
Section: Appendectomymentioning
confidence: 99%
“…28 Other environmental risk factors In observational studies, appendectomies appear to provide a risk reduction in the development of UC. 29 Oral contraceptives statistically significantly increased the risk for developing CD and appeared to increase the risk of UC. 30 The other important environmental factor playing on the development of IBD is diet control.…”
Section: Introductionmentioning
confidence: 96%